2018
DOI: 10.12659/msm.905393
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA Cancer Susceptibility Candidate 2a (CASC2a) Is a Marker of Early Recurrence After Radical Cystectomy in Patients with Urothelial Carcinoma of the Bladder

Abstract: BackgroundThe aim of this study was to investigate the expression of long non-coding RNAs (lncRNA) cancer susceptibility candidate 2a (CASC2a) in patients with urothelial carcinoma of the bladder (UCB) and its predictive value in the recurrence of UCB after radical cystectomy (RC).Material/MethodsTumor and paired adjacent normal tissues were obtained from 112 patients with UCB who underwent RC in our hospital from March 2010 to March 2012. The expression of CASC2a was evaluated by quantitative reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The down-regulation of CASC2 might contribute to malignant progression of bladder cancer. The study performed by Li et al indicated that the bladder cancer patients with low expression of CASC2 were more likely to undergo malignant disease progression and postoperative recurrence [28]. Pei er al.…”
Section: Discussionmentioning
confidence: 99%
“…The down-regulation of CASC2 might contribute to malignant progression of bladder cancer. The study performed by Li et al indicated that the bladder cancer patients with low expression of CASC2 were more likely to undergo malignant disease progression and postoperative recurrence [28]. Pei er al.…”
Section: Discussionmentioning
confidence: 99%
“…However, many lncRNAs are important for tumor size suppression. CASC2a is highly negatively correlated with pathological T and N stages, and tumor size [ 190 ]. HCG22 expression correlates with pathological stage, metastasis, and a large tumor range [ 26 ].…”
Section: Lncrnas Are Associated With Clinicopathological Characteristicsmentioning
confidence: 99%
“…The results of prognosis analysis revealed that high expression of CASC9 [ 102 , 148 ], SNHG3 [ 137 ], and SOX2OT [ 185 ], and low expression of LBCS [ 186 ] predict poor DFS. Elsewhere, high expression of CASC2a [ 190 ] increased the 5-year RFS rate, and high expression of 8 lncRNAs predicted a low RFS rate [ 21 , 23 , 37 , 38 , 115 , 146 , 156 , 164 , 188 , 193 ]. In addition, lower expression of 7 lncRNAs predicted shorter OS [ 24 , 26 , 57 , 126 , 150 , 152 , 186 ].…”
Section: Lncrnas That Influence Patient Prognosismentioning
confidence: 99%
“…For example, miRNA-125b could be a prognostic marker in recurrent hepatocellular carcinoma as its levels are significantly lower in the early stages than in the late stages of recurrence [19]. LncRNA CASC2a is identified as not only a prognosis biomarker but also a potential therapeutic target in the early recurrence of bladder cancer [20].…”
Section: Introductionmentioning
confidence: 99%